2015
DOI: 10.1111/febs.13523
|View full text |Cite
|
Sign up to set email alerts
|

miR‐330‐5p inhibits proliferation and migration of keratinocytes by targeting Pdia3 expression

Abstract: The microRNAs (miRNAs) are a class of small non-coding RNA molecules that play important roles in cellular processes by regulating gene expression at the post-transcriptional level. In skin biology, several miRNAs have been shown to be associated with differentiation, migration and apoptosis of keratinocytes, and regulation of the hair cycle. Although the biological role of miR-330-5p has been reported in several cancers and cells, the function and molecular mechanism of miR-330-5p in skin keratinocytes have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 26 publications
(32 reference statements)
1
19
1
1
Order By: Relevance
“…MiR-326/330-5p can regulate numerous of target genes. Recent study indicated that miR-330-5p inhibits proliferation and migration of keratinocytes by targeting Pdia3 expression [52], and regulates tyrosinase and PDIA3 expression and suppresses cell proliferation and invasion in cutaneous malignant melanoma [48]. MiR-326 reverses chemoresistance in human lung adeno-carcinoma cells by targeting specificity protein 1 [53], and regulates cell proliferation and migration in lung cancer by targeting phox2a and is regulated by HOTAIR [54].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-326/330-5p can regulate numerous of target genes. Recent study indicated that miR-330-5p inhibits proliferation and migration of keratinocytes by targeting Pdia3 expression [52], and regulates tyrosinase and PDIA3 expression and suppresses cell proliferation and invasion in cutaneous malignant melanoma [48]. MiR-326 reverses chemoresistance in human lung adeno-carcinoma cells by targeting specificity protein 1 [53], and regulates cell proliferation and migration in lung cancer by targeting phox2a and is regulated by HOTAIR [54].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-126 regulates cytosolic TLR signalling and modulates the duration and intensity of such signalling in DCs (Rogers and Herzog 2014). Finally, miR-330 also regulates the activity of the PI3K/Akt signalling pathway and also exerts an inhibitory effect on T cell proliferation and NK cell activation (Grigoryev et al 2011; Kim et al 2015a; Petty et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…PDIA3 also contributes to neurite outgrowth by modulating ER calcium release and cytoplasmic dynamics (LeBlanc & Nemere, 2014). Overexpression of PDIA3 in mice facilitates the regeneration of sciatic nerve after mechanical injury (Castillo et al, 2015), while PDIA3 inhibition in mouse keratinocytes decreases their ability of proliferation and migration (Kim, Yoo, Choi, & Yoon, 2015). However, in central nervous system, PDIA3 would not cross the blood-brain barrier to act directly on hippocampus.…”
Section: Introductionmentioning
confidence: 99%